MicroRNA Machinery Genes as Novel Biomarkers for Cancer - Huang, Jing-Tao; Wang, Jin; Srivastava, Vibhuti; Sen, Subrata; Liu, Song-Mei (Frontiers in Oncology, 2014)
MicroRNAs (miRNAs) directly and indirectly affect tumorigenesis. To be able to perform their myriad roles, miRNA machinery genes, such as Drosha, DGCR8, Dicer1, XPO5, TRBP, and AGO2, must generate precise miRNAs. These genes have specific expression patterns, protein-binding partners, and biochemical capabilities in different cancers. Our preliminary analysis of data from The Cancer Genome Atlas consortium on multiple types of cancer revealed significant alterations in these miRNA machinery genes. Here, we review their biological structures and functions with an eye towards understanding how they could serve as cancer biomarkers.